A dictionary of earth sciences. - Allaby, Michael (Oxford paperback reference., 2008)
Covers topics such as climatology, economic geology, geochemistry, oceanography, palaeontology, petrology, and volcanology. Includes entries on planetary science, remote sensing, statistics, and sequence stratigraphy, wind strength scales, material, temporal, and chronostratigraphic units, geologic, lunar, and Martian time scales.